Management of severe traumatic brain injury in regions with limited resources (2021)
Importance: Severe traumatic brain injury (sTBI) is a critical health problem in regions of limited resources (RLRs). Younger populations are among the most impacted. The objective of this review is to analyze recent consensus-based algorithms, protocols and guidelines proposed for the care of patients with TBI in RLRs. Observations: The principal mechanisms for sTBI in RLRs are road traffic injuries (RTIs) and violence. Limitations of care include suboptimal or non-existent pre-hospital care, overburdened emergency services, lack of trained human resources, and surgical and intensive care. Low-cost neuromonitoring systems are currently in testing, and formal neurotrauma registries are forming to evaluate both long-term outcomes and best practices at every level of care from hospital transport to the emergency department (ED), to the operating room and intensive care unit (ICU). Conclusions and Relevance: The burden of sTBI is highest in RLRs. As working-age adults are the predominantly affected age-group, an increase in disability-adjusted life years (DALYs) generates a loss of economic growth in regions where economic growth is needed most. Four multi-institutional collaborations between high-income countries (HICs) and LMICs have developed evidence and consensus-based documents focused on capacity building for sTBI care as a means of addressing this substantial burden of disease.